Non Residential Solid Waste Reduction in Krembangan District, North Surabaya - Talent Nia Pramestyawati; I. D. A. A. Warmadewanthi (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2020)
Reduction of non-residential solid waste is important because it can reduce the generation of solid waste in Benowo Landfill. Krembangan District is one of the districts in North Surabaya that was chosen as a research area however, there is no data about the existing and reduction potential of non-residential solid waste in Krembangan District. The purposes of this research are the identification of existing and reduction potential of non-residential solid waste in Krembangan District. There are 21 samples for this research. Public facility samples contain education facilities, offices, worship places, commercial places, medical centres and street sweeping. Total generation of solid waste from public facilities is 10.179,74 kg/day. Existing reduction of solid waste in source and transfer station are 158,1 kg/day and 472,53 kg/day. The reduction potential of non-residential solid waste is based on the optimal recovery factor. Reduction potential with composting and recycling activities are 3.668,31 kg/day and 694,67 kg/day.